Pre-service Science Teachers' Perceptions about Demarcation of Science from Pseudoscience - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2009)
Due to increasing interest in science, theories and claims are placed in the media. However, theories and claims involving pseudoscientific expressions mislead individuals and cause some misconceptions about science. By taking that problem into consideration, evaluating the perceptions and competencies of teacher candidates about the issue of demarcation becomes a need simply because they are educated for science classes that are assumed to be the most proper contexts to prepare the individuals for such discussions. With this in mind, this demarcation is taken as the problem of this research. Open ended questions, a sample case and interviews performed by randomly selected 11 candidates constituted the data sources of the research in which 57 freshman candidates participated. Results showed that most of the participants perceive science as being provable on one hand and as a discipline that examines everything on the other. Also, they seem to lack skills necessary to examine science-pseudoscience difference critically which results in deficiencies in such an important demarcation.
Keywords: Teacher candidates; pseudoscientific; nature of science; STUDENTS; CONCEPTIONS; VIEWS